COMPARISON OF EFFECTIVENESS OF STANDARD TRIPLE THERAPY VERSUS BISMUTH-BASED THERAPY FOR THE MANAGEMENT OF PEPTIC ULCER DISEASE DUE TO HELICOBACTER PYLORI - BAIG, MIRZA MISBA ALI; PARVEEN, UZMA; FAROOQ, RUQAIAH; TABASSUM, MAIMUNA; NAAZ, FATIMA; IBRAHIM HASSAN, SYED (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Helicobacter pylori is the primary agent causing peptic ulcer, therefore imposing a significant impact on health elated quality of life, consequently affecting nearly 50% of global population. The objective of this study is to determine and assess the effectiveness of triple therapy versus bismuth containing quadruple therapy for eradication of peptic ulcer disease due to H. pylori. Methods: A prospective randomized observational study was conducted at Princess Esra Hospital, Department of Gastroenterology for a period of 6 months. A total of 100 patients were randomly allocated in tow groups. The data were assessed using various parameters. H. pylori eradication was validated using rapid urease test done at the start treatment 4 weeks after the completion. Results: A total of 100 patients were recruited in the study. In triple therapy group medication adherence rate was found to be 82% in triple and 92% in quadruple therapy. The eradication rate was assessed using Chi-square test it was 82% and 97% in triple and quadruple therapy group, respectively. Hence, the difference was found to be statistically significant value <0.005. In addition, increased recurrence rate has been observed in triple therapy (17%) in contrast with quadruple therapy (2%). Conclusion: Addition of bismuth to significant triple therapy improves cure rates with minimal side effects. Interestingly, we observed that when bismuth was added, it produced a significant higher eradication rate (97%) when compared with standard triple therapy (82%). According to our study, bismuth is highly effective treatment of peptic ulcer disease.